Electrochemical performance of CNTs/RGO/MnO2 composite material for supercapacitor. (11th October 2016) - Lu, Liquan; Xu, Shengming; An, Junwei; Yan, Shaohui
In this article, the novel carbon materials (carbon nanotubes (CNTs) and graphene) with high-specific area and superior mechanical behavior are employed to strengthen the specific capacitance and cyclical stability of manganese dioxide (MnO2 ) for supercapacitors. The electrode material, synthesized by the CNTs, reduced graphene oxide (RGO), and MnO2 (CNTs-RGO-MnO2 composite), is characterized by scanning electron microscope, transmission electron microscope, and X-ray powder diffraction. The results indicate that the MnO2 particles are compactly distributed on the surface of the RGO and CNTs. The state of MnO2 in the CNTs/RGO/MnO2 composite is δ-MnO2 . The electrochemical test results indicate that the specific electric capacities of the CNTs/RGO/MnO2 composite are 404 F/g, 255 F/g, and 82 F/g, respectively, at 1 A/g, 3 A/g, and 10 A/g ampere densities, which illustrate that the addition of the CNTs and RGO greatly hoists the specific capacitance of the MnO2 . Moreover, the long-time charge–discharge test results indicate that the specific capacitance of the CNTs/RGO/MnO2 composite remains 70% after 5000 circles under the big current density of 30 A/g. The electrochemical impedance spectroscopy test results show that the RGO and CNTs can remarkably reduce the electric charge shifting resistance; at the same time, the electrolyte resistance and electric charge shifting resistance after the charge–discharge test are scarcely increasing, showing that the CNTs/RGO/MnO2 composite is a kind of supercapacitor electrode material with stable structure, which has the prospect of industrialization.